Correlation among oil, protein and lysine in opaque-2 Kernels - Ruschel, Renato (Pesquisa Agropecuaria Brasileira, 2014)
Correlation coefficients were calculated between percent of oil, protein, and lysine in germ, and protein, and lysine in endosperm of opaque-2 kernels from 44 ears selected to represent a wide range for oil content. ln the germ, oil and protein were negatively associated. Percent of protein in kernel was positively correlated with percent of lysine in kernel and negatively correlated with lysine as a percent of protein in kernel. Significant correlations between oil and germ size or percent indicate that selection for high oil in opaque-2 maize should increase the germ in size, and as a proportion of the kernel. Concluding from the correlation coefficients, selection for high oil should also increase the percentage of protein and lysine in the kernel. On the average one-third of the kernel protein was located in the germ. The germ was higher than the endosperm in percent of protein and lysine as a percent of protein. However, due to the relative larger endosperm size, the percentage of protein in the endosperm was more important in determining the percentage of lysine in the kernel than the percentage of protein in the germ. The weight of lysine was approximately equal in the germ and endosperm. Rather large variability associated with high values were found for the variables measured suggesting opportunities for selection.